Is there a Corruption-effect on Conspicuous Consumption?. (August 2014) - Gokcekus, Omer; Suzuki, Yui
This study empirically explores the following issue: Does corruption fuel conspicuous consumption? It examines the existence and magnitude of any potential corruption-effect on conspicuous consumption expenditure. Regression analyses of an unbalanced panel data for 20 OECD countries between 2004 and 2010 indicate that luxury car sales are higher by 191 per cent in a country with a high perceived corruption level, for example, CPI score of 4.5, as compared to a country with a low perceived corruption level, for example, CPI score of 9.0, ceteris paribus. JEL Classification: D12; D73